(untitled) (Surkhet Journal, 2023)
Butterfly diversity changes with habitat and meteorological factors. They are facing threats due to many environmental and anthropogenic causes so need their diversity and status investigation to initiate conservation programs. The butterfly diversity study was conducted at Kakrebihar protected forest, the first government protected forest, during January to December 2021. The data was collected using Ocular Point Observation Method. Capture and release method along with photography was used for butterfly identification. Total of 431 individuals of 33 species of butterflies were recorded belonging to 24 genera and 7 families. Among recorded families of butterflies, Nymphalidae was dominant family followed by family Hisperiidae. Among recorded butterfly species, 17 species were very common, 15 were common and one was rare. The total butterfly diversity and evenness were recorded to be high in the study area. The butterfly diversity was found to be high during post-monsoon season followed by monsoon and pre-monsoon season and its lowest during winter season.